2020
DOI: 10.17113/ftb.58.02.20.6337
|View full text |Cite
|
Sign up to set email alerts
|

Dromedary Milk Protein Hydrolysates Show Enhanced Antioxidant and Functional Properties

Abstract: Research background. Milk protein hydrolysates have received particular attention due to their health-promoting effects. Dromedary milk differs from the milk of other dairy animals in the composition and structure of its protein components, which give it unique properties. The bioactivity and functionality of whole dromedary milk proteins and their enzymatic hydrolysates have not received much attention, hence this study aims to investigate the effect of enzymatic hydrolysis of dromedary milk proteins on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…It was found that acid extraction of milk enables the production of milk fractions that have lower TPC than the equivalent skim milk, while TPC contents of water/ethanol extracts show higher values of TPC than those obtained in HCl/ethanol extracts with a significant variability between fractions. While many authors have reported on the antioxidant activities of various milk forms, including liquid milk ( 16 , 30 ), fermented milk ( 15 ), milk hydrolysates ( 16 , 31 ), and heat-treated milk ( 30 ), there is a relative scarcity of reports focusing on sweet, acid whey, or casein fractions ( 17 , 25 ). Moreover, within the same milk species, the outcomes fluctuated depending on the specific antioxidant assay employed (DPPH assay, ABTS assay, iron-binding capacity) and the kind of product studied (unprocessed milk, processed dairy products, or milk extracts).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that acid extraction of milk enables the production of milk fractions that have lower TPC than the equivalent skim milk, while TPC contents of water/ethanol extracts show higher values of TPC than those obtained in HCl/ethanol extracts with a significant variability between fractions. While many authors have reported on the antioxidant activities of various milk forms, including liquid milk ( 16 , 30 ), fermented milk ( 15 ), milk hydrolysates ( 16 , 31 ), and heat-treated milk ( 30 ), there is a relative scarcity of reports focusing on sweet, acid whey, or casein fractions ( 17 , 25 ). Moreover, within the same milk species, the outcomes fluctuated depending on the specific antioxidant assay employed (DPPH assay, ABTS assay, iron-binding capacity) and the kind of product studied (unprocessed milk, processed dairy products, or milk extracts).…”
Section: Discussionmentioning
confidence: 99%
“…As seen in Table (1), if infant formula becomes an option to replace breastfeeding, much effort must be made to closely mimic the nutritional profile of human breast milk for normal infant growth and development (Martin et al, 2016). According to Codex Alimentarius and European Commission regulations, the levels of macronutrients and micronutrients in infant formula must be specified to simulate the composition of breast milk (Oussaief et al, 2020). Formula composition and functionality must include and balance protein content and profile, i.e., predominant whey protein profile and αlactalbumin fortification; the profile of fatty acids, the content of carbohydrates, vitamins and minerals with those in breast milk (Drapala et al, 2016).…”
Section: Infant and Follow-on Formulaementioning
confidence: 99%
“…Its popularity is because it has become one of the most promising foods regards to its potential antioxidant and antimicrobial activities derived from caseins and whey proteins (Osman et al, 2015 andJrad et al, 2020). Camel milk differs from the milk of other species and is closest to human milk, especially in terms of its lack of β-lactoglobulin and the low amounts of κ-casein, which makes it a suitable diet for people with cow's milk protein allergy (Hochwallner et al, 2014;zibaee et al, 2015;Jrad et al, 2020 andOussaief et al, 2020). Furthermore, it was reported that camel milk is rich in vitamin C, iron and potassium contents and low in fat and lactose contents (Gopal et al, 2017).…”
Section: Non-bovine Milk As a Base Of Infant Formula Camel Milk And I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the higher similarity of camel and goat milks in composition to human milk compared to cow milk (Table 1), infant formulas have been predominantly manufactured using camel and goat milks and their proteins to provide a suitable protein source that is healthier and more easily digestible for infants [17,[21][22][23]. Camel milk is distinct from the milk of other species and bears a resemblance to human milk, owing to its low levels of κ-casein and the absence of β-lactoglobulin.…”
Section: Introductionmentioning
confidence: 99%